2018
DOI: 10.1007/s11661-018-4726-9
|View full text |Cite
|
Sign up to set email alerts
|

On Shear Testing of Single Crystal Ni-Base Superalloys

Abstract: Shear testing can contribute to a better understanding of the plastic deformation of Ni-base superalloy single crystals. In the present study, shear testing is discussed with special emphasis placed on its strengths and weaknesses. Key mechanical and microstructural results which were obtained for the high-temperature (T % 1000°C) and low-stress (s % 200 MPa) creep regime are briefly reviewed. New 3D stereo STEM images of dislocation substructures which form during shear creep deformation in this regime are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The specimens created using the presented method can also be used for many other and more detailed characterization techniques if the high‐throughput character is softened or the measurements are limited to a‐priori‐identified interesting composition ranges. This includes micro‐pillar compression, nano‐indentation and creep, in‐situ micro shear testing [ 79 ] or oxide layer stability screening by oxidation heat treatment and subsequent Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The specimens created using the presented method can also be used for many other and more detailed characterization techniques if the high‐throughput character is softened or the measurements are limited to a‐priori‐identified interesting composition ranges. This includes micro‐pillar compression, nano‐indentation and creep, in‐situ micro shear testing [ 79 ] or oxide layer stability screening by oxidation heat treatment and subsequent Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…As a striking new result, it was found that from 0.5% onwards, the [112](111) shear system deforms significantly faster than the shear system [011](111), as shown in Figure 3 (see also strain vs. time data in [12]). The corresponding logarithmic shear rate plotted as a function of shear strain is presented in Figure 3b.…”
Section: Mechanical and Micro Mechanical Analysismentioning
confidence: 86%
“…After heat treatment and prior to creep, the average γ'-volume fractions were 72% and 77% in the dendritic and interdendritic regions, respectively [13,14]. In the present work, we used a shear creep test technique, which was recently documented [12]. The SX material was first mounted onto a goniometer and oriented into a specific crystallographic direction using a Laue system from Multiwire Laboratories (Lansing, NY, USA), equipped with an electronic position control unit and a sensitive real-time back reflection camera of type MWL120.…”
Section: Materials and Shear Creep Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent years, microshear testing, which represents a kind of simple shear deformation, has received much more attention and has been studied by many researchers [85][86][87][88][89]. Metallic single crystals are widely used to perform microshear experiments because the initial crystallographic orientations of the specimens are specific and crystals with no grain boundaries have no influence on interactions with adjacent grains.…”
Section: Research On Metallic Single Crystals Under Microshearmentioning
confidence: 99%